2018
DOI: 10.3389/fimmu.2018.02052
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of in vivo Virus Engineered Dendritic Cells From Bench to Bedside: A Bumpy Road

Abstract: Dendritic cells (DCs) are recognized as highly potent antigen-presenting cells that are able to stimulate cytotoxic T lymphocyte (CTL) responses with antitumor activity. Consequently, DCs have been explored as cellular vaccines in cancer immunotherapy. To that end, DCs are modified with tumor antigens to enable presentation of antigen-derived peptides to CTLs. In this review we discuss the use of viral vectors for in situ modification of DCs, focusing on their clinical applications as anticancer vaccines. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 179 publications
(177 reference statements)
0
18
0
Order By: Relevance
“…These can selectively recognize and kill cancer cells irrespective of their location, and can form an immunological memory, ready to act when cancer cells with the same properties pop up. Activation of CTLs requires tumor antigen presentation in MHC-I molecules and co-stimulation by professional APCs of which DCs have been extensively studied for cancer vaccination 56,159.…”
Section: Therapeutic Application Of Nanobodies and Nanobody Derivativmentioning
confidence: 99%
“…These can selectively recognize and kill cancer cells irrespective of their location, and can form an immunological memory, ready to act when cancer cells with the same properties pop up. Activation of CTLs requires tumor antigen presentation in MHC-I molecules and co-stimulation by professional APCs of which DCs have been extensively studied for cancer vaccination 56,159.…”
Section: Therapeutic Application Of Nanobodies and Nanobody Derivativmentioning
confidence: 99%
“…An additional platform that could benefit from CDLV technology is in vaccinology, where researchers are developing methods to express antigens in APCs in situ. 10 LV vectors have been investigated extensively for this purpose and it has been shown that a lack of pre-existing immunity allows repeated administrations. 11 However, a potential limitation of LV use for APC transduction is the expression of SAMHD1 (SAM and HD domain-containing deoxynucleoside triphosphate triphosphohydrolase 1) in these immune cells, which lowers intracellular dNTP pools and reduces transduction efficiency by restricting the activity of RT.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Additionally, the possibility to target antigen-presenting cells (APCs) with LV vectors has been explored for vaccine development. 10 , 11 Use of a transient mRNA delivery system in a LV context could offer a significant development in these areas of research, avoiding any issues related to persistence of IDLV or IPLV vector genomes.…”
Section: Introductionmentioning
confidence: 99%
“…19,22 Interestingly, some of the inherited shortcomings of AV, such as immunity evoked against the AV capsid and low-level expression of AV genes, may now prove beneficial for the development of anticancer immunotherapies, where inducing immunity against cancer or directly killing the cancer cell is the goal. 74,75 The combined immunity against the AV and the short time of expression may prove beneficial for using AV to develop potential vaccines. 76,77 Work with AV vectors is done using BSL-2 practices.…”
Section: Adenovirus Vectorsmentioning
confidence: 99%